PANCOAST TUMOR : A CASE REPORT - Epriyanto Tri Darmadi; Ivan Tjokrowinoto (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction: Pancoast tumor, or superior sulcus tumor, is defined as a tumor that grows on the thoracic inlet or grows on a pleuropulmonary peak that is found beyond the initial cost. These tumors may invade upper ribs, muscle, vertebral, subclavian vessels, the inferior portion of brachial plexus, sympathetic nervous system, and stellate ganglion. Pancoast tumors are mostly caused by non-small cell lung cancer. Case description: A 59-year-old man came to the emergency room with complaints about a lack of pain in his left chest. Other symptoms reported by the patient include chest discomfort, stiffness, pain rising and subsiding on the left arm that may spread back and forth, and weight loss. Chest CT Scan with contrast shows a heterogeneous mass appears at the tip of the left lung, pushing the upper lobe of the left lung, bronchiectasis at the lower lobe of the left lung, destruction of the left coastal bones 1, 2, and 3, and tracheobronchial supero-inferior lymphadenopathy. Anatomical pathology results round cell tumors favor adenocarcinoma with poorly differentiated metastasis Discussion: Diagnosis of Pancoast tumor is supported by patient symptoms, imaging results, and biopsies. This patient's complaints and symptoms are unusual, leading doctors to believe that the cause is not a Pancoast tumor. Keep in mind that Pancoast Tumors aren't the only thing that can cause Pancoast syndrome, though they are the most common. The results of this patient's biopsy rule out other causes of Pancoast tumor and are consistent with the cause of Pancoast tumors, namely adenocarcinoma, a type of non-small cell lung cancer. Conclusion: Chronic and progressive complaints and unintentional weight loss become